Effect of acupuncture and moxibustion on the immune function of patients with malignant tumors: a systematic review and meta-analysis - Wang, Yan; Sui, Bailu; Zhang, Ying; Fang, Liyuan; Xie, Yi; Fang, Yuhang; Wang, Runxi (Frontiers in Immunology, 2025)
BackgroundAcupuncture and moxibustion have been shown to be safe and effective methods for bidirectional immunomodulatory function. Clinical practice and many studies have shown that acupuncture and moxibustion have a certain clinical effect on immune promotion in patients with malignant tumors.MethodsEight electronic databases were searched systematically for articles published through December 31, 2024. Study Selection Randomized controlled trial studies (RCTs) that reported The number of T lymphocytes cells in patients with malignant tumors who received acupuncture and/or moxibustionon treatment were included. For continuous variables, effect estimates were calculated as mean difference (MD); and for dichotomous variables, the risk ratio (RR) was calculated. A funnel plot was used to analyze potential publication bias.Results33 studies involving 2610 participants were included. Patients who received acupuncture and/or moxibustion treatment had higher CD3+, CD4+, CD4+/CD8+ and natural killer (NK) cell levels, but lower CD8+ levels. At the same time, the anti-tumor treatment effect was better than that of the control group.ConclusionsEvidence from this meta-analysis, acupuncture and moxibustion can enhance the immune function and improve the prognosis of malignant tumor patients. Further studies are recommended to support and confirm these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023465759.